Pemberdayaan Masyarakat dalam Bidang Ekonomi Kreatif dan Sektor Pangan Guna Rintis Kemandirian Ekonomi di Desa Banyuanyar Lor Kabupaten Probolinggo - Verto Septiandika; Imam Sucahyo; Renny Candradewi Puspitarini; Andhi Nur Rahmadi; Nur Cholifa (Universitas Medan Area, 2022)
Banyuanyar Lor Village is one of the villages in the Probolinggo Regency, East Java. Most of the residents of this village make a living as onion farmers. At least 85 percent of the residents are shallots farmers. shallots farmers play an important role in maintaining the sustainability of Probolinggo Regency as a producer of shallots that have economic advantage as in the community system, processing, and processing of shallots. Shallots are of the strategic commodities that are produced periodically and are superior in this village. Unfortunately, these agricultural products have limited added value. Shallots, if not sold directly, are only processed as snacks, additional spices, and others whose marketing is not yet wide enough. Combining village advantages and agricultural potential and empowering women, socialization activities that open opportunities for collaboration in the field of community service are carried out. This socialization activity was inserted with processed red onion products in the form of cookies created by the creativity of students participating in KKN. This socialization activity is a collaboration of major post-pandemic themes such as